The Efficacy of Lerek Fruits (Phrynium maximum)Extract Related Body Weight, Lipid Profile and Leptin in Wistar Rats-Induced High Fat Diet - Radiyati Umi Partan; Rachmat Hidayat; Yeni Agustin; Mgs Irsan Saleh; Nita Parisa; Evi Lusiana; Nia savitri Tamzil; Ayeshah Agusta Rosdah; Abdulwahab Hakimi (HM Publisher, 2017)
Background Phrynium maximum (local name : lerek ) is a plant native to Sumatera, Malaya and Borneo. This plants have a potential as a local wisdom for therapeutics. In Sumatera, Lerek was used as traditional treatment for fever, diarrhea, diabetics and for wound healing. Aim of Study Aim of this study to explore the efficacy of lerek fruits extract in body weight, lipid profile and leptin level in Wistar Rats-Induced High Fat Diet Methods This study was an experimental study , pre-post test with control group design. The sample in this study was 30 male rats, 8 weeks old, weight 150-200 gram. Rats were given high fat diet and lerek fruits extract at dose of 50, 100 and 200 mg/kgBW/day for 2 weeks. Lerek fruits was extracted by infusion methods. The results of this study were assayed by SPSS 18. Results Lerek fruit extract 100 mg/kgBW was more potent to reduce body weight gain, triglyseride level and leptin level than lerek fruit extract 50 mg/kgBW, 200 mg.kgBW, negative control and positive control. Conclusion Lerek fruit extracts had a potention to reduce body weight, triglyceride and leptin level. Keywords: Lerek fruit extract – body weight- triglyserida - leptin